The Models of Community Participation towards Madrasa in Rural Regions: A Case Study of Madrasa in Soppeng Regency - Hasyim Haddade (STAI DDI Makassar, 2022)
This research investigates the models of community participation towards madrasa (Islamic schools) in rural regions. This mainly discusses how the models of community participation towards madrasa in Soppeng regency. The results of this study eventually show: First, the participation of community towards madrasa is diverse depending on what kinds of factors influence them. However, in some aspects, they consider madrasa must be both improved and empowered as well. Secondly, most of factors influencing the community participations towards madrasa are ideological, theological, sociological, academic, and economical factors. Third, the models of community participations towards madrasa bring the quality change. Fourth, the efforts of madrasa to improve and support the community participation include several ways. The implication of this research theoretically emphasizes that madrasa in South Sulawesi, particularly considered as educational institution with community based education, still needs strategic efforts of gaining better quality related to both physical environment and educational system. On the other side, it stresses the participation of community still needs to improve whether by madrasa committee, board of education, students’ parents and teachers association, or alumni organization.